An integrated management system for occupational health and safety and environment in an operating nuclear power plant in East China and its management information system. (10th May 2018) - Sui, Yang; Ding, Rui; Wang, Hanqing
Abstract: In order to implement the integration management of the occupational health and safety and environment (OHSE) in an operating nuclear power plant (ONPP) in East China and help it pass the OHSAS 18001 and ISO 14001 certifications simultaneously rather than separately, an integrated management system (IMS) for OHSE in the ONPP consisting of the occupational health and safety and environment management manual (OHSEMM) and its supportive documents was established to cover the OHSAS 18001 and ISO 14001 standards and IAEA's safety standards on management systems. The management information system for the IMS for the ONPP in East China (MISIMSONPPEC) consisting of the core zone, which includes the information-sharing platform (ISP) and the functional management system (FMS), client and background system was designed for the first time by using browser/server (B/S) structure to overcome the difficulties in implementing the IMS. The applications of the MISIMSONPPEC in the ONPP show that it helped to share and statistically analyze the OHSE data and information from the IMS, to improve the cooperation between departments, to enhance the efficiency of management, and to pass the OHSAS 18001 and ISO 14001 certifications simultaneously rather than separately; and it helped accomplish the integration management of the OHSE in the ONPP. Highlights: The process for implementing the IMS was formulated by using the PDCA cycle. The IMS for OHSE in the ONPP consisting of the OHSEMM and its supportive documents was established. The MISIMSONPPEC consisting of the core zone, the client and the background system was designed. The core zone included the ISP and the FMS and provided functions for implementing the IMS. The MISIMSONPPEC helped to pass the OHSAS 18001 and ISO 14001 certifications simultaneously.